Positive electrode active material, positive electrode comprising the same, and lithium secondary battery
Patent Information
- Application Number
- CN202580021446.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2024-03-26
- Filing Date
- 2025-03-10
- Publication Date
- 2026-10-16
AI Technical Summary
然而,由于LiFePO4具有低电导率,因此存在当LiFePO4用作正极活性材料时电池的内阻增加的问题
[0036] The positive electrode active material of the present invention comprises a lithium iron phosphate-based compound having an olivine structure; and a carbon (C)-containing coating portion formed on the lithium iron phosphate-based compound. Since the positive electrode active material satisfies a graphitization degree of 1.00 to 1.50 according to Formula 1 described herein and a Dip(χ) of 0.160 to 0.185 according to Formula 2 described herein in the Raman spectrum measured by a Raman spectrometer, it adjusts the amount of disordered or defective carbon in the coating portion of the positive electrode active material and controls the coating efficiency, thus having an effect on improving the capacity characteristics of the battery comprising it.
Smart Images

Figure CN122935824A_ABST
Abstract
Description
[0001] Cross-reference to related applications
[0002] This application claims priority to Korean Patent Application No. 10-2024-0040833, filed on March 26, 2024, the disclosure of which is incorporated herein by reference. Technical Field
[0003] This invention relates to positive electrode active materials, positive electrodes including positive electrode active materials, and lithium secondary batteries. Background Technology
[0004] With recent technological advancements and increased demand for mobile devices and electric vehicles, the need for secondary batteries as an energy source has increased significantly. Among these secondary batteries, lithium-ion batteries, characterized by high energy density, high voltage, long cycle life, and low self-discharge rate, have been commercialized and are widely used.
[0005] Lithium-ion batteries consist of four main components: the positive electrode, the negative electrode, the separator, and the electrolyte. Among these, the positive electrode active material plays a crucial role in determining the battery's capacity, output, and lifespan. To achieve high energy density, output, and lifespan in lithium-ion batteries, improvements in the performance of the positive electrode active material are necessary; therefore, extensive research has recently been conducted to develop high-performance positive electrode active materials.
[0006] Lithium transition metal oxides, such as lithium cobalt-based oxides (e.g., LiCoO2), lithium nickel-based oxides (e.g., LiNiO2), lithium manganese-based oxides (e.g., LiMnO2 or LiMn2O4), and lithium iron phosphate-based compounds (e.g., LiFePO4), have been developed as positive electrode active materials for lithium secondary batteries. More recently, lithium composite transition metal oxides including two or more transition metals, such as Li[Ni], have also been developed. a Co b Mn c O2, Li[Ni a Co b Al c ]O2 and Li[Ni a Co b Mn c Al d O2 has been developed and is widely used.
[0007] Because lithium iron phosphate-based compounds with an olivine structure have the best structural stability, they exhibit excellent lifetime characteristics and are promising active materials with superior advantages in all aspects of safety, including overcharge and over-discharge.
[0008] In particular, LiFePO4 exhibits excellent high-temperature stability due to the strong binding force of PO4, is cheaper than LiCoO2, LiNiO2, or LiMn2O4 due to its abundant and inexpensive iron content, and has a low environmental impact due to its low toxicity. However, because LiFePO4 has low electrical conductivity, there is a problem of increased internal resistance in the battery when it is used as the positive electrode active material. Therefore, due to the increased polarization potential when the battery circuit is closed, there is a problem of reduced battery capacity.
[0009] To address this problem, there is an urgent need to develop positive electrode active materials with improved capacity properties by appropriately doping or coating lithium iron phosphate-based compounds.
[0010] [Existing Technical Documents]
[0011] [Patent Literature]
[0012] (Patent Document 1) Korean Patent Application Publication No. 10-2023-0142687 Summary of the Invention
[0013] Technical issues
[0014] One aspect of the present invention provides a positive electrode active material having improved capacity characteristics.
[0015] Another aspect of the present invention provides a positive electrode and a secondary battery that have excellent capacity characteristics by including the above-described positive electrode active material.
[0016] Technical solution
[0017] (1) The present invention provides a positive electrode active material comprising a lithium iron phosphate-based compound having an olivine structure; and a carbon (C) coating portion formed on the lithium iron phosphate-based compound, wherein the degree of graphitization according to Formula 1 is 1.00 to 1.50 in the Raman spectrum measured by a Raman spectrometer, and the Dip(χ) according to Formula 2 is 0.160 to 0.185.
[0018] [Formula 1]
[0019] Degree of graphitization = I D / I G
[0020] [Equation 2]
[0021] Dip(χ) = I G - I x
[0022] In Equations 1 and 2, I D It is the maximum peak intensity of the D band, IG It is the maximum peak intensity of the G spectral band, and I x It represents the intensity of the minimum point between the G and D bands, where the D band is at 1300 cm⁻¹. -1 Up to 1400cm -1 The peak appears at the Raman shift, and the G band is at 1550 cm⁻¹. -1 Up to 1650cm -1 The peak value that appears at the Raman shift.
[0023] (2) The present invention provides the positive electrode active material of (1) above, wherein the ratio of manganese to all transition metals in the lithium iron phosphate-based compound is more than 30 mol%.
[0024] (3) The present invention provides a positive electrode active material of any one of (1) and (2) above, wherein the lithium iron phosphate-based compound has a composition represented by chemical formula 1.
[0025] [Chemical Formula 1]
[0026] Li 1+x Fe 1-a-b Mn a M 1 b PO4
[0027] In chemical formula 1, M 1 It is selected from at least one of the following groups: aluminum (Al), magnesium (Mg), nickel (Ni), cobalt (Co), titanium (Ti), gallium (Ga), copper (Cu), vanadium (V), niobium (Nb), zirconium (Zr), cerium (Ce), indium (In), zinc (Zn), and yttrium (Y), and -0.5 ≤ x ≤ 0.5, 0.3 ≤ a < 1.0, and 0 ≤ b ≤ 0.1.
[0028] (4) The present invention provides a positive electrode active material of any one of (1) to (3) above, wherein the amount of carbon contained in the coating portion is 1.00% to 2.50% by weight based on the total weight of the positive electrode active material.
[0029] (5) The present invention provides a positive electrode active material of any one of (1) to (4) above, wherein the degree of graphitization is 1.00 to 1.10.
[0030] (6) The present invention provides a positive electrode active material as described in any one of (1) to (5) above, wherein the Dip(χ) is 0.170 to 0.180.
[0031] (7) The present invention provides a positive electrode active material according to any one of (1) to (6) above, wherein the average particle size (D) 50 The thickness ranges from 0.25 μm to 0.45 μm.
[0032] (8) The present invention provides a positive electrode active material of any one of (1) to (7) above, wherein the average crystallite size is 110.0 nm to 145.0 nm.
[0033] (9) The present invention provides a positive electrode comprising any one of the positive electrode active materials described in (1) to (8) above.
[0034] (10) The present invention provides a lithium secondary battery comprising the positive electrode described above [9].
[0035] Beneficial effects
[0036] The positive electrode active material of the present invention comprises a lithium iron phosphate-based compound having an olivine structure; and a carbon (C)-containing coating portion formed on the lithium iron phosphate-based compound. Since the positive electrode active material satisfies a graphitization degree of 1.00 to 1.50 according to Formula 1 described herein and a Dip(χ) of 0.160 to 0.185 according to Formula 2 described herein in the Raman spectrum measured by a Raman spectrometer, it adjusts the amount of disordered or defective carbon in the coating portion of the positive electrode active material and controls the coating efficiency, thus having an effect on improving the capacity characteristics of the battery comprising it.
[0037] Therefore, positive electrodes and secondary batteries containing the above-mentioned positive electrode active materials have the advantage of improved capacity characteristics. Attached Figure Description
[0038] Figure 1 These are the Raman spectra of each positive electrode active material prepared in the examples and comparative examples. Detailed Implementation
[0039] The invention will be described in more detail below to allow for a clearer understanding of it.
[0040] It should be understood that the words or terms used in the specification and claims should not be construed as having the meaning defined in a common dictionary, and it should also be understood that, based on the inventor's ability to appropriately define the meaning of words or terms to best explain the principles of the invention, the words or terms should be construed as having a meaning consistent with their meaning in the relevant field and in the context of the technical idea of the invention.
[0041] It should also be understood that the terms "comprising," "including," or "having" in this specification specify the presence of the stated features, numbers, steps, elements, or combinations thereof, but do not exclude the presence or addition of one or more other features, numbers, steps, elements, or combinations thereof.
[0042] The term "on" in this specification means not only the case where one component is directly formed on the upper surface of another component, but also the case where there may be intermediate components.
[0043] In this specification, Raman spectra are obtained by placing the sample in a universal DXR holder, pressing the sample with a glass slide to pretreat it so that the surface height of the sample is uniform, and measuring the portion corresponding to the 415 μm x 300 μm area of the sample placed in the DXR holder using an Ar ion laser with a laser wavelength of 532 nm using a Raman spectrometer (HORIBA Scientific, XploRA).
[0044] In this specification, I D During Raman spectroscopy analysis at approximately 1300 cm⁻¹ -1 Up to 1400cm -1 The maximum peak intensity of the D band appearing at the Raman shift, and I G During Raman spectroscopy analysis at approximately 1550 cm⁻¹ -1 Up to 1650cm -1 The maximum peak intensity of the G band appears at the Raman shift. In Raman spectroscopy, there may be a minimum point between the G and D bands. The minimum point refers to the wavelength with the lowest intensity between the G and D bands in the Raman spectrum. In this specification, I... x This represents the minimum value, specifically the intensity of the minimum point.
[0045] In this specification, graphitization degree refers to the extent to which amorphous carbon is partially or completely transformed into crystalline graphite, which can be confirmed using Raman spectroscopy, and the structure of carbon-based materials can be analyzed using graphitization degree. During Raman spectral analysis of carbon-based materials, the G band represents the sp of the carbon-based material. 2 The peaks of the bonds indicate the absence of structural defects in carbon crystals, and the D band represents the sp of carbon-based materials. 3 The peak of the key, where when sp 2 The atomic bonds that form a bond break to form sp 3 When bonding occurs, the peak of the D band increases. Since the D band increases when disorder or defects are generated in carbon-based materials, the maximum peak intensity (Ig) of the D band can be calculated. D ) and the maximum peak intensity of the G band (I G The ratio of (I) D / I G This can be used to quantitatively assess the degree of disorder or defects in carbon crystals.
[0046] In this specification, Dip(χ) refers to the difference between the maximum peak intensity of the G band and the intensity of the minimum point between the G and D bands.
[0047] In this specification, the amount of carbon (C) relative to the total weight of the positive electrode active material (wt%) can be measured by TC-IC (Total Carbon - Inorganic Carbon) analysis using an additive and subtractive carbon analyzer (Primacs, Skalar Analytical BV). Specifically, it is a method of measuring total carbon and inorganic carbon to calculate the difference as organic carbon.
[0048] In this specification, "microcrystal" refers to a particle unit having substantially the same crystal orientation.
[0049] In this specification, X-ray diffraction (XRD) analysis can be used to quantitatively analyze the average crystallite size using copper (Cu) Kα X-rays. Specifically, the average crystallite size can be quantitatively analyzed by placing the particle to be measured in a holder and analyzing the diffraction pattern produced by irradiating the particle with X-rays. The test sample is prepared by placing the powder sample of the target particle into the groove in the middle of a holder for general powders, leveling the surface using a sliding glass, and ensuring that the sample height is the same as the edge of the holder. Then, X-ray diffraction analysis is performed using a Bruker D8-Endeavor (light source: Cu-Kα line, wavelength: 1.54 Å) equipped with a LynxEye XE-T position-sensitive detector, with a step size of 0.02°, a step time of 0.2 seconds, and a total scan time of approximately 30 minutes, using a fixed divergence slit (FDS) of 0.5° and a 2θ range of 15° to 80°. The measured data underwent Rietveld refinement, taking into account the charge at each site (+3 for metal ions at transition metal sites and +2 for Ni ions at Li sites) and cation mixing. Instrument broadening during crystallite size analysis was accounted for using the fundamental parameter method (FPA) implemented in the Bruker TOPAS program, and the entire peak within the measurement range was used during fitting. Peak shapes were fitted using only the Lorentz component of the first principle (FP) peak type available in TOPAS, and strain was not considered in this case.
[0050] In this specification, the average particle size (D) 50The particle size distribution (D) can be defined as the particle size at 50% of the volumetric cumulative distribution on a particle size distribution curve (a graph of particle size distribution). After dispersing the target powder in a dispersion medium, the dispersion medium is introduced into a commercial laser diffraction particle size analyzer (e.g., Microtrac, Microtrac S3500). The particle size distribution is calculated by measuring the difference in the diffraction pattern caused by particle size as the particles pass through the laser beam. The average particle size (D) can be measured by calculating the particle size at 50% of the volumetric cumulative distribution using the analyzer. 50 ).
[0051] Positive electrode active material
[0052] The positive electrode active material according to the present invention will be described below.
[0053] The positive electrode active material according to the present invention comprises a lithium iron phosphate-based compound having an olivine structure; and a carbon (C) coating portion formed on the lithium iron phosphate-based compound, wherein the degree of graphitization is 1.00 to 1.50 according to Formula 1 in the Raman spectrum measured by a Raman spectrometer, and the Dip(χ) is 0.160 to 0.185 according to Formula 2.
[0054] [Formula 1]
[0055] Degree of graphitization = I D / I G
[0056] [Equation 2]
[0057] Dip(χ) = I G - I x
[0058] In Equations 1 and 2, I D It is the maximum peak intensity of the D band, I G It is the maximum peak intensity of the G spectral band, and I x It represents the intensity of the minimum point between the G and D bands, where the D band is at 1300 cm⁻¹. -1 Up to 1400cm -1 The peak appears at the Raman shift, and the G band is at 1550 cm⁻¹. -1 Up to 1650cm -1 The peak that appears at the Raman shift.
[0059] The inventors have discovered that when a positive electrode active material comprising a lithium iron phosphate-based compound having an olivine structure and a carbon (C) coating formed on the lithium iron phosphate-based compound has a graphitization degree of 1.00 to 1.50 according to Formula 1 as described in this specification and a Dip(χ) of 0.160 to 0.185 according to Formula 2 as described in this specification in a Raman spectrum measured by a Raman spectrometer, the number of electrons that can be inserted and extracted increases within an appropriate range due to the increase of free electrons in the coating, and the coating efficiency is excellent. Therefore, the capacity characteristics of a lithium secondary battery including the positive electrode active material can be improved, thus leading to the completion of the present invention.
[0060] When the positive electrode active material comprising a lithium iron phosphate-based compound having an olivine structure and a carbon (C) coating formed on the lithium iron phosphate-based compound has a graphitization degree of less than 1 according to Formula 1 as described in this specification in the Raman spectrum measured by a Raman spectrometer, there is a problem of insufficient free electrons in the carbon layer due to less disordered or defective carbon. Furthermore, when the graphitization degree of Formula 1 as described in this specification is greater than 1.5, there is a problem of poor lifetime characteristics due to excessive disordered or defective carbon. When the Dip(χ) of Formula 2 as described in this specification is greater than 0.185, the following problems exist: the coating acts as a resistor due to the excessive carbon contained in the coating, the coating coverage is low, and the charge / discharge capacity at room temperature is low. And when the Dip(χ) of Formula 2 as described in this specification is less than 0.160, there is a problem of low charge / discharge capacity at room temperature. Furthermore, when the degree of graphitization is less than 1.00 and Dip(χ) is greater than 0.185, there is a problem of poor capacity characteristics. This is because the coating part with relatively few free electrons in the carbon layer exists excessively and unevenly on the lithium iron phosphate-based compound.
[0061] In this invention, the degree of graphitization is evaluated and expressed as a parameter represented by Equation 1 below. The degree of graphitization mentioned in this invention is based on the maximum peak intensity of the G band (IG). G ) and the maximum peak intensity of the D band (I D The value of graphitization is adjusted, and the greater the amount of disordered or defective carbon on the surface of lithium iron phosphate-based compounds, the greater the value of graphitization.
[0062] For example, for carbon-based materials that do not contain disordered or defective carbon, the degree of graphitization is 0 because there is no maximum peak in the D band.
[0063] [Formula 1]
[0064] Degree of graphitization = I D / I G
[0065] In Equation 1, I D It is the maximum peak intensity of the D band, I G This represents the maximum peak intensity of the G band, while the D band appears at 1300 cm⁻¹. -1 Up to 1400cm -1 The peak at the Raman shift, and the G band appears at 1550 cm⁻¹. -1 Up to 1650cm -1 The peak value at the Raman shift.
[0066] The degree of graphitization of the positive electrode active material according to Formula 1 is 1.00 to 1.50. Specifically, the degree of graphitization can be 1.00 or more, or 1.01 or more, and can be 1.04 or less, 1.05 or less, 1.06 or less, 1.07 or less, 1.08 or less, 1.09 or less, 1.10 or less, 1.20 or less, 1.30 or less, 1.40 or less, or 1.50 or less. When the degree of graphitization meets the above range, the number of electrons that can be inserted and extracted increases due to the increase of free electrons in the carbon layer to an appropriate level, and there is an effect of improving capacity characteristics. In particular, when the degree of graphitization is in the range of 1.00 to 1.10, it has the effect of better electrical conductivity while maintaining physical and chemical stability.
[0067] In this invention, the coating efficiency is evaluated by the amount of carbon contained in the coating and the coverage of the coating, and is expressed as a parameter represented by the following Equation 2. The Dip(χ) mentioned in this invention is based on the maximum peak intensity (I) of the G band. G ) and the intensity of the minimum point between the G band and the D band (I x The value of Dip(χ) is adjusted as follows: the greater the carbon content in the coating or the lower the coverage of the coating, the greater the value of Dip(χ).
[0068] Coating efficiency represents the relationship between the amount of carbon contained in the coating and the coverage of the coating. Specifically, high coating efficiency means that the carbon-containing coating formed on the lithium iron phosphate-based compound has a high coverage while minimizing the amount of carbon in the coating. High coverage of the coating means that the coating is continuous and formed in a manner with uniform thickness and composition.
[0069] For example, when the amount of carbon contained in the coating is small and the coverage of the coating is high, Dip(χ) and the maximum peak intensity of the G band (I) G There is no difference.
[0070] [Equation 2]
[0071] Dip(χ) = I G - I x
[0072] In Equation 2, I G It is the maximum peak intensity of the G spectral band, and I x It is the intensity of the minimum point between the G and D spectral bands, where the G band is at 1550 cm⁻¹. -1 Up to 1650cm -1 The peak value that appears at the Raman shift.
[0073] The Dip(χ) of the positive electrode active material according to Formula 2 is from 0.16 to 0.185. Specifically, Dip(χ) can be 0.160 or more, 0.161 or more, 0.162 or more, 0.163 or more, 0.164 or more, 0.165 or more, 0.166 or more, 0.167 or more, 0.168 or more, 0.169 or more, 0.170 or more, 0.171 or more, or 0.172 or more, and can be 0.179 or less, 0.180 or less, 0.181 or less, 0.182 or less, 0.183 or less, 0.184 or less, or 0.185 or less. When Dip(χ) satisfies the above range, since it improves the electronic conductivity of the positive electrode active material without acting as a resistor, the capacity characteristics are improved. In particular, when Dip(χ) is in the range of 1.170 to 1.180, ion movement is promoted because the coating does not interfere with the insertion and deintercalation reactions of lithium ions and electrons.
[0074] According to embodiments of the present invention, the ratio of manganese in the total transition metals of the lithium iron phosphate-based compound can be 30 mol% or more. The ratio of manganese in the total transition metals of the lithium iron phosphate-based compound can be 30 mol% or more, 35 mol% or more, 40 mol% or more, 45 mol% or more, 50 mol% or more, 55 mol% or more, or 60 mol% or more, and can be 65 mol% or less, 70 mol% or less, 75 mol% or less, 80 mol% or less, 85 mol% or less, 95 mol% or less, or 99 mol% or less. When the manganese ratio is within the above range, high energy density can be exhibited, thus achieving high capacity characteristics.
[0075] According to one embodiment of the present invention, the lithium iron phosphate-based compound may have a composition represented by the following chemical formula 1.
[0076] [Chemical Formula 1]
[0077] Li 1+x Fe 1-a-b Mn a M 1 b PO4
[0078] In chemical formula 1, M 1It is selected from at least one of the following groups: aluminum (Al), magnesium (Mg), nickel (Ni), cobalt (Co), titanium (Ti), gallium (Ga), copper (Cu), vanadium (V), niobium (Nb), zirconium (Zr), cerium (Ce), indium (In), zinc (Zn), and yttrium (Y), and -0.5 ≤ x ≤ 0.5, 0.30 ≤ a < 1.00, and 0 ≤ b ≤ 0.1.
[0079] M 1 It is a dopant element, where M 1 It is selected from at least one of Al, Mg, Ni, Co, Ti, Ga, Cu, V, Nb, Zr, Ce, In, Zn, and Y. M is not necessarily included. 1 However, when M is included in an appropriate amount 1 This can improve the particle shape of the positive electrode active material and improve the stability of the crystal structure.
[0080] x can be greater than or equal to -0.5, greater than or equal to -0.4, greater than or equal to -0.3, greater than or equal to -0.2, greater than or equal to -0.1, or greater than or equal to 0, and can also be less than or equal to 0.1, less than or equal to 0.2, less than or equal to 0.3, less than or equal to 0.4, or less than or equal to 0.5. When x meets the above ranges, high capacity characteristics and high energy density per unit volume can be achieved.
[0081] 'a' represents the mole fraction of manganese (Mn) in all metals other than lithium in the lithium iron phosphate-based compound, where 'a' can be 0.30 or more, 0.35 or more, 0.40 or more, 0.45 or more, 0.50 or more, 0.55 or more, or 0.60 or more, and can be 0.65 or less, 0.70 or less, 0.75 or less, 0.80 or less, 0.85 or less, 0.90 or less, 0.95 or less, or less than 1.00. When 'a' is within the above range, the capacity characteristics of the positive electrode active material can be improved. In particular, when 'a' is in the range of 0.30 to 0.65, the structural stability and operating voltage range of the positive electrode active material can be improved, and the energy density can be increased.
[0082] b is M among all metals other than lithium in lithium iron phosphate-based compounds. 1 The mole fraction of b, where b can be 0.00 or more, 0.01 or more, 0.02 or more, 0.03 or more, 0.04 or more, or 0.05 or more, and can be less than 0.06, less than 0.07, less than 0.08, less than 0.09, or less than 0.10. When b is within the above range, the particle shape of the positive electrode active material can be improved, the stability of the crystal structure can be improved, and the capacity characteristics can be improved by improving the conductivity.
[0083] 1-ab is the molar fraction of iron (Fe) in all metals other than lithium in lithium iron phosphate-based compounds. When 1-ab is within the range described above, the capacity characteristics of the cathode active material can be improved. In particular, when 1-ab is in the range of 0.35 to 0.70, the structural stability and thermal stability of the cathode active material can be improved.
[0084] According to an embodiment of the present invention, the carbon content in the coating portion can be from 1.00 wt% to 2.50 wt% based on the total weight of the positive electrode active material. Specifically, the carbon content in the coating portion can be 1.00 wt% or more, 1.10 wt% or more, 1.20 wt% or more, 1.30 wt% or more, 1.40 wt% or more, 1.50 wt% or more, 1.60 wt% or more, 1.70 wt% or more, or 1.80 wt% or more, and can be 2.20 wt% or less, 2.30 wt% or less, 2.40 wt% or less, or 2.50 wt% or less. When the amount of carbon is within the above range, the coating portion can improve the electronic conductivity of the positive electrode active material without acting as a resistor.
[0085] According to embodiments of the present invention, the coating portion can be a film type, an island type, or a combination thereof. The film type can be continuous, and the island type can be discontinuous. In particular, when the coating portion is a film type, the capacity characteristics can be improved because the lithium ion mobility can be increased.
[0086] According to embodiments of the present invention, the positive electrode active material may have an average particle size (D) of 0.25 μm to 0.45 μm. 50 Specifically, the average particle size (D) 50 The particle size can be ≥0.25μm, ≥0.26μm, ≥0.27μm, ≥0.28μm, ≥0.29μm, or ≥0.3μm, and can be ≤0.32μm, ≤0.33μm, ≤0.34μm, ≤0.35μm, ≤0.36μm, ≤0.37μm, ≤0.38μm, ≤0.39μm, ≤0.4μm, ≤0.41μm, ≤0.42μm, ≤0.43μm, ≤0.44μm, or ≤0.45μm. The average particle size (D...) 50 Within the above range, the electrode density can be increased.
[0087] According to embodiments of the present invention, the positive electrode active material may have an average crystallite size of 110.0 nm to 145.0 nm. Specifically, the average crystallite size may be 110.0 nm or more, and may be 140.0 nm or less, 141.0 nm or less, 142.0 nm or less, 143.0 nm or less, 144.0 nm or less, or 145.0 nm or less. When the average crystallite size is within the above range, the lifetime characteristics can be improved due to the reduction of side reactions between the positive electrode active material and the electrolyte solution, and the resistance characteristics can be improved due to the shortening of the lithium diffusion path within the particles.
[0088] The positive electrode active material of the present invention can be prepared by the following methods. For example, the positive electrode active material can be prepared by mixing raw materials and sintering the mixture. Mixing can be carried out by dry mixing or wet mixing. In the case of mixing each component by dry mixing, the sintering process can be carried out without a separate drying process. In the case of mixing the components by wet mixing, the components can be added to a solvent, especially water or a mixture of water and an organic solvent (especially alcohols, etc.) that can be uniformly mixed with water, or after preparing a solution containing each raw material, especially an aqueous solution, the components mixed by mixing these solutions are spray-dried and then sintered. Each raw material can be used in an appropriate amount, taking into account the amount of each metal element in the final lithium iron phosphate-based compound.
[0089] According to an embodiment of the present invention, after preparing a slurry by mixing lithium-containing raw materials, phosphorus-containing raw materials, iron-containing raw materials and manganese-containing raw materials, a positive electrode active material can be prepared by further mixing a carbon-containing raw material with the slurry and then sintering the mixture.
[0090] Specifically, the positive electrode active material of the present invention can be prepared by the following steps: (a) preparing a slurry by mixing lithium-containing raw materials, phosphorus-containing raw materials, iron-containing raw materials and manganese-containing raw materials with a solvent; (b) preparing a mixture by mixing the slurry with carbon-containing raw materials and sintering the mixture.
[0091] As lithium-containing raw materials, lithium sulfates, nitrates, acetates, carbonates, oxalates, citrates, halides, hydroxides, or hydroxyoxides can be used, and there are no particular restrictions on the lithium-containing raw materials, as long as they can dissolve in water. Specifically, lithium-containing raw materials can be Li₂CO₃, LiNO₃, LiNO₂, LiOH, LiOH·H₂O, LiH, LiF, LiCl, LiBr, LiI, CH₃COOLi, Li₂O, Li₂SO₄, CH₃COOLi, or Li₃C₆H₅O₇, and any one of them or a mixture of two or more of them can be used.
[0092] The phosphorus-containing (P) raw material can be at least one selected from (NH4)3PO4, NH4H2PO4, LiH2PO4 and H3PO4, and any one of them or a mixture of two or more of them can be used.
[0093] Iron (Fe)-containing raw materials can be selected from at least one of iron-containing oxides, sulfur oxides, carbonates, nitrates and phosphates, and any one of them or a mixture of two or more of them can be used.
[0094] The manganese (Mn)-containing raw material can be selected from at least one of MnSO4, MnCO3, Mn2O3, MnO2, Mn3O4, Mn(NO3)2, manganese acetate, manganese dicarboxylate, manganese citrate, manganese salts of fatty acids, manganese hydroxy oxides and manganese halides such as manganese chloride, and any one of them or a mixture of two or more of them can be used.
[0095] Water, or a mixture of water and an organic solvent (specifically, alcohols, etc.) that is homogeneous with water, can be used as a solvent.
[0096] During the preparation of the slurry in step (a), raw materials containing doped elements, such as zirconium-containing raw materials or yttrium-containing raw materials, may be further mixed.
[0097] According to the present invention, in step (a), the lithium-containing raw material, the phosphorus-containing raw material, the iron-containing raw material and the manganese-containing raw material can be mixed in amounts having the composition expressed by Formula 1 as described in this specification.
[0098] The carbon-containing raw material can be at least one selected from sucrose, glucose, polyethylene glycol, polyvinyl alcohol, and polyvinyl acetate.
[0099] Based on the total weight of the positive electrode active material, carbon-containing raw materials can be mixed in amounts ranging from 1% to 7% by weight.
[0100] Step (b) can be prepared by sintering a mixture at a temperature of 600°C to less than 730°C to prepare a positive electrode active material comprising a lithium iron phosphate-based compound; and a carbon-containing coating portion on the lithium iron phosphate-based compound, wherein the coating portion comprises amorphous carbon and is a film type, an island type, or a combination thereof.
[0101] The positive electrode active material that satisfies the degree of graphitization according to Formula 1 and the Dip(χ) according to Formula 2, as described in this specification, can be prepared by the above method. The degree of graphitization and Dip(χ) are technical characteristics that arise by comprehensively adjusting the type of raw materials, sintering temperature, and mixing amount of raw materials.
[0102] positive electrode
[0103] Next, the positive electrode according to the present invention will be described.
[0104] The positive electrode according to the present invention comprises a positive electrode active material layer containing the positive electrode active material according to the present invention. Specifically, the positive electrode comprises a positive electrode current collector and a positive electrode active material layer formed on the positive electrode current collector and comprising the positive electrode active material. Since the positive electrode active material has been described above, its detailed description will be omitted, and only the remaining configurations will be described in detail below.
[0105] The positive electrode current collector is not particularly limited, as long as it is conductive and does not cause chemical changes in the battery. Materials used include, for example, stainless steel, aluminum, nickel, titanium, sintered carbon or aluminum, or stainless steel surface-treated with carbon, nickel, titanium, silver, etc. Furthermore, the positive electrode current collector typically has a thickness from 3 μm to 500 μm, and microscopic irregularities can be formed on its surface to improve the adhesion of the positive electrode active material. The positive electrode current collector can be used in various shapes, such as membranes, sheets, foils, meshes, porous bodies, foams, nonwoven fabrics, etc.
[0106] In addition to the positive electrode active material, the positive electrode active material layer may also contain a conductive agent and a binder. In this case, based on the total weight of the positive electrode active material layer, the content of the positive electrode active material can be from 80% to 99% by weight, more specifically from 85% to 98.5% by weight, and excellent capacity characteristics can be obtained within this range.
[0107] Conductive agents are used to provide conductivity to the electrodes. Any conductive agent can be used without particular limitation, as long as it has suitable electronic conductivity without causing chemical changes in the battery. Specific examples of conductive agents can be graphite, such as natural or artificial graphite; carbon-based materials, such as carbon black, acetylene black, Ketjen black, channel black, furnace black, lamp black, thermal black, and carbon fibers; powders or fibers of metals (such as copper, nickel, aluminum, and silver); conductive whiskers, such as zinc oxide whiskers and potassium titanate whiskers; conductive metal oxides, such as titanium oxide; or conductive polymers, such as polyphenylene derivatives, and any one or a mixture of two or more of them. Based on the total weight of the positive electrode active material layer, the binder content can be from 0.1% by weight to 15% by weight.
[0108] The adhesive improves the adhesion between the positive electrode active material particles and the adhesion between the positive electrode active material and the current collector. Specific examples of the adhesive can be polyvinylidene fluoride (PVDF), polyvinylidene fluoride-hexafluoropropylene copolymer (PVDF-co-HFP), polyvinyl alcohol, polyacrylonitrile, carboxymethyl cellulose (CMC), starch, hydroxypropyl cellulose, regenerated cellulose, polyvinylpyrrolidone, polytetrafluoroethylene, polyethylene, polypropylene, ethylene-propylene-diene polymer (EPDM), sulfonated EPDM, styrene-butadiene rubber (SBR), fluororubber, or various copolymers thereof, and any one of them or a mixture of two or more of them can be used. Based on the total weight of the positive electrode active material layer, the adhesive content can be from 0.1% by weight to 15% by weight.
[0109] The positive electrode can be prepared according to typical methods for preparing a positive electrode, the difference being the use of the aforementioned positive electrode active material. Specifically, a positive electrode active material layer-forming composition, prepared by dissolving or dispersing the aforementioned positive electrode active material, along with optional binders and conductive agents, in a solvent, is applied to a positive electrode current collector. The positive electrode is then obtained by drying and rolling the coated positive electrode current collector. In this case, the type and amount of the positive electrode active material, binder, and conductive agent are the same as those previously described. Alternatively, as another method, the positive electrode can be prepared by casting the positive electrode active material layer-forming composition onto a separate carrier, and then pressing the film layer, separated from the carrier, onto the positive electrode current collector.
[0110] The solvent can be one commonly used in the art and can include dimethyl sulfoxide (DMSO), isopropanol, N-methylpyrrolidone (NMP), acetone, or water, and any one of them or a mixture of two or more of them can be used. Considering the coating thickness and manufacturing yield of the slurry, the amount of solvent used can be sufficient if it can dissolve or disperse the positive electrode active material, conductive agent, and binder, and can allow for a viscosity that provides excellent thickness uniformity during subsequent coatings used to prepare the positive electrode.
[0111] Lithium secondary batteries
[0112] Next, the lithium secondary battery according to the present invention will be described.
[0113] This invention can prepare an electrochemical device including a positive electrode. The electrochemical device can specifically be a battery or a capacitor, and more specifically a lithium secondary battery.
[0114] A lithium secondary battery specifically includes a positive electrode, a negative electrode facing the positive electrode, a separator disposed between the positive and negative electrodes, and an electrolyte. Since the positive electrode is the same as described above, its detailed description will be omitted, and only the remaining configurations will be described in detail below.
[0115] In addition, the lithium secondary battery may optionally include a battery container that houses an electrode assembly containing a positive electrode, a negative electrode and a separator, as well as a sealing member that seals the battery container.
[0116] In a lithium secondary battery, the negative electrode includes a negative electrode current collector and a layer of negative electrode active material disposed on the negative electrode current collector.
[0117] There are no particular restrictions on the negative electrode current collector, as long as it has high conductivity without causing chemical changes in the battery. Materials such as copper, stainless steel, aluminum, nickel, titanium, sintered carbon, copper, or stainless steel surface-treated with carbon, nickel, titanium, silver, etc., as well as aluminum-cadmium alloys, can be used. Furthermore, the negative electrode current collector typically has a thickness from 3 μm to 500 μm and, similar to the positive electrode current collector, can form microscopic irregularities on its surface to improve the adhesion of the negative electrode active material. For example, the negative electrode current collector can be used in various shapes, such as films, sheets, foils, meshes, porous bodies, foams, and nonwoven fabrics.
[0118] In addition to the negative electrode active material, the negative electrode active material layer may optionally include a binder and a conductive agent.
[0119] Compounds capable of reversibly inserting and deintercalating lithium can be used as anode active materials. Specific examples of anode active materials can be carbonaceous materials, such as artificial graphite, natural graphite, graphitized carbon fibers, and amorphous carbon; metallic compounds that can form alloys with lithium, such as silicon (Si), aluminum (Al), tin (Sn), lead (Pb), zinc (Zn), bismuth (Bi), indium (In), magnesium (Mg), gallium (Ga), cadmium (Cd), Si alloys, Sn alloys, or Al alloys; and metal oxides that can be doped or undoped with lithium, such as SiO₂. β (0<β<2), SnO2, vanadium oxide and lithium vanadium oxide; or composite materials including metallic compounds and carbonaceous materials, such as Si-C composites or Sn-C composites, and any one or a mixture of two or more thereof can be used. Additionally, metallic lithium films can be used as the negative electrode active material. Furthermore, both low-crystallinity carbon and high-crystallinity carbon can be used as carbon materials. Typical examples of low-crystallinity carbon can be soft carbon and hard carbon, and typical examples of high-crystallinity carbon can be irregular, planar, sheet-like, spherical or fibrous natural or artificial graphite, Kish graphite, pyrolytic carbon, mesophase pitch-based carbon fibers, mesophase carbon microspheres, mesophase pitch and high-temperature sintered carbon, such as coke derived from petroleum or coal tar pitch.
[0120] Based on the total weight of the negative electrode active material layer, the content of the negative electrode active material can be from 80% to 99% by weight.
[0121] Adhesives are components that facilitate adhesion between conductive materials, active materials, and current collectors. Based on the total weight of the negative electrode active material layer, adhesives are typically added in amounts ranging from 0.1% to 10% by weight. Examples of adhesives include polyvinylidene fluoride (PVDF), polyvinyl alcohol, carboxymethyl cellulose (CMC), starch, hydroxypropyl cellulose, regenerated cellulose, polyvinylpyrrolidone, polytetrafluoroethylene, polyethylene, polypropylene, ethylene-propylene-diene polymer (EPDM), sulfonated EPDM, styrene-butadiene rubber, nitrile rubber, fluororubber, and various copolymers thereof.
[0122] A conductive agent is a component used to further improve the conductivity of the negative electrode active material. Based on the total weight of the negative electrode active material layer, the content of the conductive agent can be less than 10% by weight, specifically less than 5% by weight. There are no particular limitations on the conductive agent, as long as it is conductive without causing chemical changes in the battery. For example, conductive materials such as: graphite, such as natural or artificial graphite; carbon black, such as acetylene black, Ketjen black, channel black, furnace black, lamp black, and thermal black; conductive fibers, such as carbon fibers or metal fibers; fluorocarbons; metal powders, such as aluminum powder and nickel powder; conductive whiskers, such as zinc oxide whiskers and potassium titanate whiskers; conductive metal oxides, such as titanium oxide; or polyphenylene derivatives.
[0123] A composition for forming a negative electrode active material layer is prepared by dissolving or dispersing an optional binder and conductive agent, along with a negative electrode active material, in a solvent and drying the coated negative electrode current collector. The negative electrode active material layer can be prepared by coating the negative electrode active material layer forming composition onto the negative electrode current collector, or by casting the negative electrode active material layer forming composition onto a separate carrier and then pressing the film layer, separated from the carrier, onto the negative electrode current collector.
[0124] In lithium-ion secondary batteries, the separator separates the negative and positive electrodes and provides a path for lithium ions to move. Any separator can be used without particular limitation, as long as it is commonly used in lithium-ion secondary batteries. Separators with high moisture retention capacity for the electrolyte and low resistance to electrolyte ion transfer are particularly preferred. Specifically, porous polymer membranes can be used, such as porous polymer membranes prepared from polyolefin-based polymers (e.g., ethylene homopolymers, propylene homopolymers, ethylene / butene copolymers, ethylene / hexene copolymers, and ethylene / methacrylate copolymers), or laminated structures having two or more layers. Furthermore, typical porous nonwoven fabrics can be used, such as nonwoven fabrics formed from high-melting-point glass fibers or polyethylene terephthalate fibers. In addition, coated separators including ceramic components or polymer materials can be used to ensure heat resistance or mechanical strength, and separators with single-layer or multi-layer structures can optionally be used.
[0125] Furthermore, the electrolyte used in this invention may include organic liquid electrolytes, inorganic liquid electrolytes, solid polymer electrolytes, gel polymer electrolytes, solid inorganic electrolytes, or molten inorganic electrolytes that can be used to prepare lithium secondary batteries, but this invention is not limited thereto.
[0126] Specifically, the electrolyte may contain organic solvents and lithium salts.
[0127] Any organic solvent can be used without particular limitation, as long as it serves as a medium through which ions involved in the electrochemical reactions of the battery can move. Specifically, ester-based solvents, such as methyl acetate, ethyl acetate, γ-butyrolactone, and ε-caprolactone; ether-based solvents, such as dibutyl ether or tetrahydrofuran; ketone-based solvents, such as cyclohexanone; aromatic solvents, such as benzene and fluorobenzene; or carbonate-based solvents, such as dimethyl carbonate (DMC), diethyl carbonate (DEC), methyl ethyl carbonate (EMC), ethylene carbonate (EC), and propylene carbonate (PC); alcohol-based solvents, such as ethanol and isopropanol; nitriles, such as R-CN (where R is a straight-chain, branched, or cyclic C2-C20 hydrocarbon group, and may include double-bonded aromatic rings or ether bonds); amides, such as dimethylformamide; dioxolane, such as 1,3-dioxolane; or sulfolane can be used as organic solvents. Among these solvents, carbonate solvents are preferred, and mixtures of cyclic carbonates (e.g., ethylene carbonate or propylene carbonate) with high ionic conductivity and high dielectric constant and low viscosity linear carbonate compounds (e.g., ethyl methyl carbonate, dimethyl carbonate, or diethyl carbonate) are even more preferred, as this can improve the charge / discharge performance of the battery. In this case, the performance of the electrolyte solution can be excellent when cyclic carbonates and linear carbonates are mixed in a volume ratio of about 1:1 to about 1:9.
[0128] Lithium salts can be used without any specific limitations, as long as they are compounds capable of providing lithium ions for lithium secondary batteries. Specifically, LiPF6, LiClO4, LiAsF6, LiBF4, LiSbF6, LiAlO4, LiAlCl4, LiCF3SO3, LiC4F9SO3, LiN(C2F5SO3)2, LiN(C2F5SO2)2, LiN(CF3SO2)2, LiCl, LiI, or LiB(C2O4)2 can be used as lithium salts. Lithium salts can be used in concentration ranges from 0.1 M to 5.0 M, particularly from 0.1 M to 3.0 M. If the concentration of the lithium salt is within the above range, excellent electrolyte performance can be obtained due to the electrolyte having suitable conductivity and viscosity, and lithium ions can move efficiently.
[0129] To improve battery life characteristics, suppress battery capacity reduction, and improve battery discharge capacity, in addition to the electrolyte components mentioned above, the electrolyte may also include at least one additive, such as compounds based on haloalkyl carbonates like difluoroethylene carbonate, pyridine, triethyl phosphite, triethanolamine, cyclic ethers, ethylenediamine, n-glycol dimethyl ether, triammonium hexaphosphate, nitrobenzene derivatives, sulfur, quinone imine dyes, N-substituted oxazolidinones, N,N-substituted imidazolides, ethylene glycol dialkyl ethers, ammonium salts, pyrrole, 2-methoxyethanol, or aluminum trichloride. In this case, based on the total weight of the electrolyte, the content of the additive can be from 0.1% by weight to 10% by weight, specifically from 0.1% by weight to 5% by weight.
[0130] Because lithium secondary batteries containing the positive electrode active material according to the invention exhibit the excellent capacity and efficiency characteristics described above, they are suitable for portable devices such as mobile phones, laptops and digital cameras, as well as electric vehicles such as hybrid electric vehicles (HEVs).
[0131] Therefore, according to another embodiment of the present invention, a battery module including a lithium secondary battery as a unit battery and a battery pack including the battery module are provided.
[0132] Battery modules or battery packs can be used as a power source for at least one medium-sized and large unit of power tools; electric vehicles, including electric vehicles (EVs), hybrid electric vehicles and plug-in hybrid electric vehicles (PHEVs); or power storage systems.
[0133] The shape of the lithium secondary battery of the present invention is not particularly limited, but it can be cylindrical, prismatic, pouch-shaped or coin-shaped.
[0134] The lithium secondary battery described in this invention can be used not only as a power source for small devices in single-cell batteries, but also as a unit battery in medium and large battery modules containing multiple single-cell batteries.
[0135] In the following, examples of the invention will be described in detail in a manner readily practiced by those skilled in the art. However, the invention can be embodied in many different forms and should not be construed as limited to the examples set forth herein.
[0136] Examples and Comparative Examples
[0137] The invention will be described in more detail below with reference to embodiments.
[0138] However, the following embodiments are only for illustrating the present invention, and the scope of the present invention is not limited thereto.
[0139] Example 1
[0140] Li₂CO₃, FePO₄, MnCO₃, and NH₄H₂PO₄ were mixed to achieve a Li:Fe:Mn:PO₄ molar ratio of 1.02:0.4:0.6:1. This mixture was then combined with water to achieve a solids concentration of 20% by weight. The mixture was then wet-milled using a bead mill or ball mill to prepare a slurry (D). 50 (0.21 μm). The slurry was then mixed with sucrose to prepare a mixture. In this case, the sucrose was mixed in an amount of 4.5% by weight based on the total weight of Li₂CO₃, FePO₄, MnCO₃, and NH₄H₂PO₄.
[0141] The mixture was spray-dried (inlet temperature 230°C, outlet temperature 95°C) and then sintered at 700°C for 10 hours in a nitrogen atmosphere to prepare a positive electrode active material, said positive electrode active material comprising LiFe 0.4 Mn 0.6 PO4 represents a lithium iron phosphate-based compound; and a carbon-containing (C) coating formed on the lithium iron phosphate-based compound. The carbon-containing coating includes amorphous carbon and is a film type.
[0142] Example 2
[0143] Li₂CO₃, FePO₄, MnCO₃, and NH₄H₂PO₄ were mixed to achieve a Li:Fe:Mn:PO₄ molar ratio of 1.02:0.4:0.6:1. This mixture was then combined with water to achieve a solids concentration of 20% by weight. The mixture was then wet-milled using a bead mill or ball mill to prepare a slurry (D). 50 (0.25 μm). The slurry was then mixed with sucrose to prepare a mixture. In this case, the sucrose was mixed in an amount of 5% by weight based on the total weight of Li₂CO₃, FePO₄, MnCO₃, and NH₄H₂PO₄.
[0144] The mixture was spray-dried (inlet temperature 230°C, outlet temperature 95°C) and then sintered at 700°C for 10 hours in a nitrogen atmosphere to prepare a positive electrode active material, said positive electrode active material comprising LiFe 0.4 Mn 0.6 PO4 represents a lithium iron phosphate-based compound; and a carbon-containing (C) coating formed on the lithium iron phosphate-based compound. The carbon-containing coating includes amorphous carbon and is a film type.
[0145] Example 3
[0146] Li₂CO₃, FePO₄, MnCO₃, and NH₄H₂PO₄ were mixed to achieve a Li:Fe:Mn:PO₄ molar ratio of 1.02:0.7:0.3:1. This mixture was then combined with water to achieve a solids concentration of 20% by weight. The mixture was then wet-milled using a bead mill or ball mill to prepare a slurry (D). 50 (0.25 μm). The slurry was then mixed with sucrose to prepare a mixture. In this case, the sucrose was mixed in an amount of 5% by weight based on the total weight of Li₂CO₃, FePO₄, MnCO₃, and NH₄H₂PO₄.
[0147] The mixture was spray-dried (inlet temperature 230°C, outlet temperature 95°C) and then sintered at 700°C for 10 hours in a nitrogen atmosphere to prepare a positive electrode active material, said positive electrode active material comprising LiFe 0.7 Mn 0.3 PO4 represents a lithium iron phosphate-based compound; and a carbon-containing (C) coating formed on the lithium iron phosphate-based compound. The carbon-containing coating includes amorphous carbon and is a film type.
[0148] Comparative Example 1
[0149] Li₂CO₃, LiH₂PO₄, FePO₄, and MnO were mixed to achieve a Li:Fe:Mn:PO₄ molar ratio of 1.02:0.4:0.6:1. This mixture was then combined with water to achieve a solids concentration of 20% by weight. The mixture was then wet-milled using a bead mill or ball mill to prepare a slurry (D). 50 (0.21 μm). The slurry was then mixed with sucrose to prepare a mixture. In this case, the sucrose was mixed in an amount of 5% by weight based on the total weight of Li₂CO₃, LiH₂PO₄, FePO₄, and MnO.
[0150] The mixture was spray-dried (inlet temperature 230°C, outlet temperature 95°C) and then sintered at 700°C for 10 hours in a nitrogen atmosphere to prepare a positive electrode active material, said positive electrode active material comprising LiFe 0.4 Mn 0.6 PO4 represents the composition of a lithium iron phosphate-based compound; and a carbon (C) coating formed on the lithium iron phosphate-based compound.
[0151] Comparative Example 2
[0152] Li₂CO₃, LiH₂PO₄, FePO₄, and Mn₃O₄ were mixed to achieve a Li:Fe:Mn:PO₄ molar ratio of 1.02:0.4:0.6:1. This mixture was then combined with water to achieve a solids concentration of 20% by weight. Finally, the mixture was wet-milled using a bead mill to prepare a slurry (D). 50(0.25 μm). The slurry was then mixed with sucrose to prepare a mixture. In this case, the sucrose was mixed in an amount of 5% by weight based on the total weight of Li₂CO₃, LiH₂PO₄, FePO₄, and Mn₃O₄.
[0153] The mixture was spray-dried (inlet temperature 230°C, outlet temperature 95°C) and then sintered at 700°C for 10 hours in a nitrogen atmosphere to prepare a positive electrode active material, said positive electrode active material comprising LiFe 0.4 Mn 0.6 PO4 represents the composition of a lithium iron phosphate-based compound; and a carbon (C) coating formed on the lithium iron phosphate-based compound.
[0154] Comparative Example 3
[0155] Li₂CO₃, FePO₄, MnCO₃, and NH₄H₂PO₄ were mixed to achieve a Li:Fe:Mn:PO₄ molar ratio of 1.02:0.4:0.6:1. This mixture was then combined with water to achieve a solids concentration of 20% by weight. The mixture was then wet-milled using a bead mill to prepare a slurry (D). 50 (0.21 μm). The slurry was then mixed with sucrose to prepare a mixture. In this case, the sucrose was mixed in an amount of 4.8% by weight based on the total weight of Li₂CO₃, FePO₄, MnCO₃, and NH₄H₂PO₄.
[0156] The mixture was spray-dried (inlet temperature 230°C, outlet temperature 95°C) and then sintered at 730°C for 10 hours in a nitrogen atmosphere to prepare a positive electrode active material, said positive electrode active material comprising LiFe 0.4 Mn 0.6 PO4 represents the composition of a lithium iron phosphate-based compound; and a carbon (C) coating formed on the lithium iron phosphate-based compound.
[0157] Comparative Example 4
[0158] Li₂CO₃, FePO₄, MnCO₃, and NH₄H₂PO₄ were mixed to achieve a Li:Fe:Mn:PO₄ molar ratio of 1.02:0.4:0.6:1. This mixture was then combined with water to achieve a solids concentration of 20% by weight. The mixture was then wet-milled using a bead mill to prepare a slurry (D). 50 (0.21 μm). The slurry was then mixed with sucrose to prepare a mixture. In this case, the sucrose was mixed in an amount of 5.2% by weight based on the total weight of Li₂CO₃, FePO₄, MnCO₃, and NH₄H₂PO₄.
[0159] The mixture was spray-dried (inlet temperature 230°C, outlet temperature 95°C) and then sintered at 730°C for 10 hours in a nitrogen atmosphere to prepare a positive electrode active material, said positive electrode active material comprising LiFe 0.4 Mn 0.6 PO4 represents the composition of a lithium iron phosphate-based compound; and a carbon (C) coating formed on the lithium iron phosphate-based compound.
[0160] Comparative Example 5
[0161] Li₂CO₃, FePO₄, MnCO₃, and NH₄H₂PO₄ were mixed to achieve a Li:Fe:Mn:PO₄ molar ratio of 1.02:0.4:0.6:1. This mixture was then combined with water to achieve a solids concentration of 20% by weight. The mixture was then wet-milled using a bead mill to prepare a slurry (D). 50 (0.25 μm). The slurry was then mixed with citric acid to prepare a mixture. In this case, the citric acid was mixed in an amount of 5.62% by weight based on the total weight of Li₂CO₃, FePO₄, MnCO₃, and NH₄H₂PO₄.
[0162] The mixture was spray-dried (inlet temperature 230°C, outlet temperature 95°C) and then sintered at 730°C for 10 hours in a nitrogen atmosphere to prepare a positive electrode active material, said positive electrode active material comprising LiFe 0.4 Mn 0.6 PO4 represents the composition of a lithium iron phosphate-based compound; and a carbon (C) coating formed on the lithium iron phosphate-based compound.
[0163] Comparative Example 6
[0164] Li₂CO₃, FePO₄, MnCO₃, and NH₄H₂PO₄ were mixed to achieve a Li:Fe:Mn:PO₄ molar ratio of 1.02:0.7:0.3:1. This mixture was then combined with water to achieve a solids concentration of 20% by weight. The mixture was then wet-milled using a bead mill or ball mill to prepare a slurry (D). 50 (0.25 μm). The slurry was then mixed with sucrose to prepare a mixture. In this case, the sucrose was mixed in an amount of 5% by weight based on the total weight of Li₂CO₃, FePO₄, MnCO₃, and NH₄H₂PO₄.
[0165] The mixture was spray-dried (inlet temperature 230°C, outlet temperature 95°C) and then sintered at 700°C for 10 hours in a nitrogen atmosphere to prepare a positive electrode active material, said positive electrode active material comprising LiFe 0.7 Mn 0.3PO4 represents a lithium iron phosphate-based compound; and a carbon-containing (C) coating formed on the lithium iron phosphate-based compound. The carbon-containing coating includes amorphous carbon and is a film type.
[0166] Experimental Example
[0167] Experimental Example 1: Raman Spectroscopy Analysis
[0168] The Raman spectra of each positive electrode active material prepared in the examples and comparative examples were analyzed using a Raman spectrometer (HORIBA Scientific, XploRA) (laser wavelength: 532 nm, Ar-ion laser). Specifically, the Raman spectra were analyzed at 1300 cm⁻¹. -1 Up to 1400cm -1 The peak appearing at the Raman shift is defined as the D band, and at 1550 cm⁻¹ -1 Up to 1650cm -1 The peak appearing at the Raman shift is defined as the G band, where the degree of graphitization according to Equation 1 below and Dip(χ) according to Equation 2 below are calculated and presented in Table 1 below. Furthermore, the Raman spectral data of the positive electrode active materials of Example 1 and Comparative Example 1, along with Dip(χ) according to Equation 2 described in this specification, are plotted as follows: Figure 1 Arrows representing Raman spectral data.
[0169] [Formula 1]
[0170] Degree of graphitization = I D / I G
[0171] [Equation 2]
[0172] Dip(χ) = I G - I x
[0173] In equations 1 and 2, I D It is the maximum peak intensity of the D band, I G It is the maximum peak intensity of the G spectral band, and I x It is the intensity of the minimum point between the G and D spectral bands.
[0174] Figure 1 These are the Raman spectra of each positive electrode active material prepared in the examples and comparative examples. Figure 1 The arrows in the text indicate Dip(χ) of each positive electrode active material prepared in Example 1 and Comparative Example 1.
[0175] [Table 1]
[0176] According to Table 1, the positive electrode active materials of Examples 1 to 3 were confirmed to have a graphitization degree of 1.00 to 1.50 according to the invention and a Dip(χ) of 0.160 to 0.185 according to the invention. In contrast, the positive electrode active materials of Comparative Examples 1 and 2 were confirmed to have a graphitization degree of less than 1.00 according to the invention and a Dip(χ) of more than 0.185 according to the invention, and the positive electrode active materials of Comparative Examples 3 and 4 were confirmed to have a graphitization degree of 1.00 to 1.50 according to the invention and a Dip(χ) of less than 0.160 or more than 0.185 according to the invention. Furthermore, the positive electrode active material of Comparative Example 5 was confirmed to have a graphitization degree of less than 1.00 according to the invention and a Dip(χ) of 0.160 to 0.185 according to the invention, and the positive electrode active material of Comparative Example 6 was confirmed to have a graphitization degree of less than 1.00 according to the invention and a Dip(χ) of more than 0.185 according to the invention.
[0177] Experimental Example 2: ICP Analysis
[0178] 3g of each positive electrode active material prepared in the examples and comparative examples were used to prepare analytical samples. Using a carbon analyzer (Primacs, Skalar Analytical BV), the analytical samples were subjected to high-temperature combustion oxidation at 1100°C to convert the carbon present in the samples into CO2, and CO2 was measured using an NDIR detector. An acidification detection IC was used, in which inorganic carbon was converted into CO2 in the IC reactor. Data were collected using the Windows-based PRIMACS MCS software, and the TOC (Total Organic Carbon) concentration of the samples was calculated using the formula TC-IC=TOC. The amount (wt%) of carbon (C) present in the analytical samples based on the total weight of the positive electrode active material is presented in Table 2 below.
[0179] Experimental Example 3: Particle Size Analysis
[0180] The average particle size (D) of each positive electrode active material prepared in the examples and comparative examples was measured using a particle size analyzer (PSA) (Microtrac, Microtrac S3500). 50 ), and is presented in Table 2 below.
[0181] Experiment Example 4: XRD Analysis
[0182] After X-ray diffraction (XRD) measurements were performed on each positive electrode active material prepared in the Examples and Comparative Examples, the average crystallite size (nm) of each positive electrode active material is presented in Table 2 below.
[0183] [Table 2]
[0184] Table 2 confirms that the amount of carbon (C) in the positive electrode active materials of Examples 1 to 3 ranges from 1.00% to 2.50% by weight based on the total weight of the positive electrode active materials, the average particle size ranges from 0.25 μm to 0.45 μm, and the average crystallite size ranges from 110.0 nm to 145.0 nm. In contrast, it is confirmed that the average crystallite size of the positive electrode active materials of Comparative Examples 1 and 2 is less than 110 nm, and the average crystallite size of the positive electrode active materials of Comparative Examples 3 to 6 is greater than 145 nm.
[0185] Experiment Example 5: Battery Characteristic Evaluation
[0186] Preparation of coin-type half-cell
[0187] A positive electrode slurry was prepared by mixing 90 wt% of each of the positive electrode active materials prepared in the examples and comparative examples, 5.0 wt% of carbon black as a conductive agent, and 5.0 wt% of polyvinylidene fluoride (PVDF) as a binder in an N-methylpyrrolidone (NMP) solvent. One surface of an aluminum current collector was coated with the above-prepared positive electrode slurry, dried at 130°C, and then rolled to prepare each positive electrode.
[0188] A lithium metal electrode is used as the negative electrode, and the electrode assembly is prepared by placing a porous polyethylene membrane between the positive and negative electrodes. A coin-shaped half-cell is prepared by placing the electrode assembly in a battery casing and then injecting an electrolyte solution in which 1.0 M LiPF6 is dissolved in an organic solvent in which ethylene carbonate (EC): ethyl methyl carbonate (EMC): diethyl carbonate (DEC) is mixed in a volume ratio of 3:4:3.
[0189] After preparing the coin-shaped half-cell, the capacity characteristics of the cell were measured using the following method.
[0190] Evaluation of battery capacity characteristics
[0191] After formation, the coin-shaped half-cell was charged at 25°C in constant current-constant voltage (CC-CV) mode (0.1 C, cutoff current: 0.05 C) to 4.25 V, and then discharged in CC mode (0.1 C) to 2.5 V. The charge and discharge capacities (mAh / g) were measured under these conditions. The measured charge and discharge capacities (mAh / g) and the percentage of discharge capacity relative to charge capacity (efficiency (%)) are presented in Table 3 below.
[0192] [Table 3]
[0193] According to Table 3, batteries containing the positive electrode active materials of Examples 1 to 3 (i.e., positive electrode active materials having a graphitization degree of 1.00 to 1.50 and a Dip(χ) of 0.160 to 0.185) were confirmed to have a charge / discharge capacity of 145.0 mAh / g or more and an efficiency of 98.5% or more at room temperature. In contrast, batteries containing the positive electrode active materials of Comparative Examples 1 and 2 (i.e., positive electrode active materials having a graphitization degree of less than 1.00 and a Dip(χ) of greater than 0.185) were confirmed to have a low charge / discharge capacity at room temperature. Furthermore, batteries containing the positive electrode active materials of Comparative Examples 3 and 4 (i.e., positive electrode active materials having a graphitization degree of 1.00 to 1.50 and a Dip(χ) of less than 0.160 or greater than 0.185) were confirmed to have low charge / discharge capacity and efficiency at room temperature. Furthermore, it was confirmed that batteries containing the positive electrode active materials of Comparative Examples 5 and 6 (i.e., positive electrode active materials with a graphitization degree of less than 1) have low efficiency at room temperature.
[0194] For reference, the battery characteristics of the cathode active material with a graphitization degree greater than 1.50 according to the present invention were not evaluated because a secondary phase in the form of Fe2P or Fe3P was generated during the preparation process by sintering the cathode active material at a high temperature above 800°C.
[0195] Therefore, it can be understood that the positive electrode active material according to the present invention can increase the number of electrons that can be inserted and extracted by adjusting the amount of disordered or defective carbon in the coating part and controlling the coating efficiency, and cause less irreversible capacity loss during charging and discharging.
Claims
1. A positive electrode active material, comprising: Lithium iron phosphate-based compounds with an olivine structure; and The carbon (C) coating formed on the lithium iron phosphate-based compound, in, In the Raman spectra measured by a Raman spectrometer, the degree of graphitization according to Equation 1 is 1.00 to 1.50, and According to Equation 2, Dip(χ) ranges from 0.160 to 0.185: [Formula 1] Degree of graphitization = I D / I G [Equation 2] Dip(χ)= I G - I x Among them, in equations 1 and 2, I D It is the maximum peak intensity of the D band, I G It is the maximum peak intensity of the G band, and I x It is the intensity of the minimum point between the G and D spectral bands. The D band is at 1300 cm⁻¹ -1 Up to 1400cm -1 The peak that appears at the Raman shift, and The G band is at 1550 cm⁻¹ -1 Up to 1650cm -1 The peak that appears at the Raman shift.
2. The positive electrode active material according to claim 1, wherein, The ratio of manganese to all transition metals in the lithium iron phosphate-based compound is 30 mol% or more.
3. The positive electrode active material according to claim 1, wherein, The lithium iron phosphate-based compound has a composition represented by chemical formula 1: [Chemical Formula 1] Li 1+x Fe 1-a-b Mn a M 1 b PO4 In chemical formula 1, M 1 It is selected from at least one of the following groups: aluminum (Al), magnesium (Mg), nickel (Ni), cobalt (Co), titanium (Ti), gallium (Ga), copper (Cu), vanadium (V), niobium (Nb), zirconium (Zr), cerium (Ce), indium (In), zinc (Zn), and yttrium (Y). -0.5≤x≤0.5, 0.3≤a<1.0, and 0.0≤b≤0.
1.
4. The positive electrode active material according to claim 1, wherein, Based on the total weight of the positive electrode active material, the amount of carbon contained in the coating portion is from 1.00% to 2.50% by weight.
5. The positive electrode active material according to claim 1, wherein, The degree of graphitization is 1.00 to 1.
10.
6. The positive electrode active material according to claim 1, wherein, The Dip(χ) is between 0.170 and 0.
180.
7. The positive electrode active material according to claim 1, wherein, The average particle size D of the positive electrode active material 50 The range is from 0.25 μm to 0.45 μm.
8. The positive electrode active material according to claim 1, wherein, The average crystallite size of the positive electrode active material is between 110.0 nm and 145.0 nm.
9. A positive electrode comprising the positive electrode active material according to any one of claims 1 to 8.
10. A lithium secondary battery comprising the positive electrode as described in claim 9.
Citation Information
Patent Citations
Rechargeable lithium battery
KR1020230142687A
Solar module including battery management system
KR1020240040833A